Bone metastases in germ cell tumours: lessons learnt from a large retrospective study. (25th June 2013) - Jamal‐Hanjani, Mariam; Karpathakis, Anna; Kwan, Amy; Mazhar, Danish; Ansell, Wendy; Shamash, Jonathan; Harper, Peter; Rudman, Sarah; Powles, Thomas; Chowdhury, Simon
<x xml:space="preserve">Abstract</x> Objective To determine the characteristics of patients with germ cell cancer and bone metastases. Patients and Methods The case records of patients with known germ cell tumours (GCTs) within the Anglian Germ Cell Cancer Group database between January 2005 and March 2011 were reviewed retrospectively. Data were collected for histopathology, presence of bone metastases at diagnosis or relapse, site of bone metastases and imaging method used to confirm bone metastases, treatment received, response to treatment and overall survival. We present here the largest unselected cohort of bone metastases in patients with GCTs. Results In all, 2550 cases of GCTs were reviewed and there was bone involvement in 19 cases. The primary site was either testicular (13/19), mediastinal (1/19) or unknown (5/19). Most cases were non‐seminomatous GCTs (11/19, 58%) and only three cases of seminomatous GCTs (3/19, 16%) with five cases in which diagnosis was based on clinical history and significantly raised GCT markers (5/19, 26%). In all of these five cases β‐human chorionic gonadotrophin was raised and in three α‐fetoprotein was raised, consistent with non‐seminomatous GCT. There were bone metastases at diagnosis (0.51%, 13/2550) or at relapse (0.24%, 6/2550). The sites of bone metastases were the vertebrae (15/19, 79%), pelvis (3/19, 16%), ribs (3/19, 16%) and femur (2/19, 11%). Ten patients (53%) had solitary, and nine patients (47%) had multiple, sites of bone metastases. In patients presenting with bone metastases at diagnosis compared with relapse, the mortality rate was 23% (3/13) and 50% (3/6), respectively. After receiving one line of chemotherapy, nine patients (47%) remained in remission not requiring further treatment, six (32%) required further chemotherapy due to subsequent relapse, three (16%) died after first‐line chemotherapy and one was lost to follow‐up. At the time of data collection and based on the last clinic follow‐up, six patients (32%) had died with a median (interquartile range, IQR) follow‐up of 11.5 (4.3, 24.8) months and 10 (53%) remained alive with a median (IQR) follow‐up of 26 (13.5, 48) months Three patients were lost to follow‐up. Of the known patients alive, eight (42%) remained in remission and two (11%) had recurrent disease requiring further treatment. Conclusion Although bone disease in germ cell cancer is rare, awareness of this condition is important and there is a need for prospective evaluation of patient characteristics, treatment approaches and survival outcome in this group of patients.